2019
DOI: 10.1007/s11191-019-00034-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complexity of Students’ Scientific Explanations and Associated Nature of Science Views Within a Place-Based Socioscientific Issue Context

Abstract: In addition to considering sociocultural, political, economic, and ethical factors (to name a few), effectively engaging socioscientific issues (SSI) requires that students understand and apply scientific explanations and the nature of science (NOS). Promoting such understandings can be achieved through immersing students in authentic real-world contexts where the SSI impacts occur and teaching those students about how scientists comprehend, research, and debate those SSI. This triangulated mixed-methods inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…The studies appearing below are at the forefront of the efforts to use place-based approaches to determine how students engage SSI through more nuanced and contextualized ways. Herman (2018) and Herman et al (2019) investigated 60 secondary students who experienced a week long field SSI instruction focused on the local SSI of wolf reintroduction in Yellowstone National Park. The SSI instruction involved interactions with wildlife ecologists who were involved with the Yellowstone wolf reintroduction and subsequent research and outreach efforts pertaining to the wolves' impact on the Yellowstone ecological and human communities.…”
Section: Ssi and The Importance Of Informal And Placebased Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies appearing below are at the forefront of the efforts to use place-based approaches to determine how students engage SSI through more nuanced and contextualized ways. Herman (2018) and Herman et al (2019) investigated 60 secondary students who experienced a week long field SSI instruction focused on the local SSI of wolf reintroduction in Yellowstone National Park. The SSI instruction involved interactions with wildlife ecologists who were involved with the Yellowstone wolf reintroduction and subsequent research and outreach efforts pertaining to the wolves' impact on the Yellowstone ecological and human communities.…”
Section: Ssi and The Importance Of Informal And Placebased Contextsmentioning
confidence: 99%
“…An umbrella term for this type educative experience is called science in context (SinC) with the goal of actively promoting the well-being of living things that are in balance with the non-living world (Bencze et al, in press). The recognition of balancing anthropocentric and ecocentric factors is further recognized in the contextualized place-based education research found in the work of Herman, Owens, Oertli, Zangori, and Newton (2019) and related ecojustice approaches to environmental education (Herman, Sadler, Zeidler, and Newton (2018).…”
Section: Introductionmentioning
confidence: 98%
“…Such “globally thinking” sentiments reflect environmental education initiatives such as those put forth by the UNESCO‐UNEP International Environmental Education Programme (Gough, 2013). Others have focused more on local or personal issues and decisions to elucidate how students should conceptualize and respond to SSI in an informed, equitable, and a civic manner (Herman, 2015, 2018; Herman et al, 2019; Kinslow et al, 2019; Zeidler et al, 2013). Two common and related themes occur across this body of scholarship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It will develop a deep understanding of how the students' scientific knowledge is generated and how the use of NOS understanding addresses the status of knowledge. It is intended that students can make decisions based on information about real-world science problems, both personal and socio-scientific (Lederman, Lederman, & Antink, 2013;Khishfe, 2012;Herman, Newton, Owens, Oertli, & Zangori, 2019), afterward students will be able to play more active and effective roles in society (Khishfe, 2012). Previous researches in various countries measured students' understanding of NOS at the high-grade level and on a large scale (Das, Faikhamta, & Punsuvon, 2017;Dogan & Abd-El-Khalick, 2008;Ryan & Aikenhead, 1992).…”
Section:  Introductionmentioning
confidence: 99%